Eculizumab-Related Abortion in a Woman with Paroxysmal Nocturnal Hemoglobinuria: A Case Report - Rodríguez-Ferreras, Adrián (J Reprod Infertil, 2019)
BACKGROUND: The use of eculizumab during pregnancy has generally been discouraged. Published data on related studies provides conflicting information and establishing a benefit-risk relationship proves to be a complicated task. Miscarriage rates, concomitant medications, and the stages of pregnancy when eculizumab treatment was initiated varied among the patients included in the case series. The aim of this report is to discuss eculizumab use during pregnancy. CASE PRESENTATION: A case of a woman diagnosed with Paroxysmal Nocturnal Hemoglobinuria (PNH) and treated with eculizumab, who expressed desire for pregnancy is presented. Six months after her eculizumab treatment, the patient experienced spontaneous abortion in her first trimester. The direct relation between eculizumab and the miscarriage is not clear. Other factors may have influenced this case, thus demonstrating the difficulty of managing pregnancy in women with PNH. CONCLUSION: Controversy on eculizumab risk during pregnancy encourages further review on its use, highlighting the importance to assess each case individually.